2019
DOI: 10.1039/c9sm00598f
|View full text |Cite|
|
Sign up to set email alerts
|

Stokesian dynamics of sedimenting elastic rings

Abstract: We study numerically the dynamics of elastic microfilaments which form closed loops and settle under gravity in a viscous fluid. We observe diversity of periodic and stationary sedimentation modes, dependent on flexibility and initial configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 77 publications
0
10
2
Order By: Relevance
“…(2020) linking extrachromosomal circular DNA properties with neuroblastoma, and partly inspired by previous numerical work using bead-spring hydrodynamic models (Gruziel-Słomka et al. 2019). Electrophoretic and ultracentrifugation measurements of mobility pose questions about what constitutes a flexible regime, correct values of drag coefficients and the stress distribution along the filament.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…(2020) linking extrachromosomal circular DNA properties with neuroblastoma, and partly inspired by previous numerical work using bead-spring hydrodynamic models (Gruziel-Słomka et al. 2019). Electrophoretic and ultracentrifugation measurements of mobility pose questions about what constitutes a flexible regime, correct values of drag coefficients and the stress distribution along the filament.…”
Section: Overviewmentioning
confidence: 99%
“…2018; Gruziel-Słomka et al. 2019) that high flexibility leads to a change in orientation (and sometimes shape) of sedimenting objects, affecting their sedimentation speed. Independently, in the case of linear filaments, Reichert & Stark (2005) observed that including elasticity can change the behaviour qualitatively when looking at bundling vs non-bundling flagella.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it would be worthwhile to study hydrodynamic interactions of pairs of sedimenting elastic loops. 46,60…”
mentioning
confidence: 99%